Study to Evaluate Prediction of Invasion in Breast Carcinoma Diagnosed on FNAC - Goswami, Alpeshpuri P; Gondaliya, Jigneshkumar Jigneshkumar; Shah, Shaila N (Annals of Pathology and Laboratory Medicine, 2019)
Background: FNAC is minimally invasive, produces a speedy result and is inexpensive than biopsy. This remains one of the most important technique from a practical point of view for diagnosis in most of breast lesion. Tubular or angular epithelial structures, malignant cells adherent to fibrous stroma, presence of intracytoplasmic lumina in malignant cells, fibroblast proliferation and fragments of elastoid stroma were predictive of invasion if associated with breast carcinoma. Objectives: To evaluate invasion criteria in fine needle aspiration cytology (FNAC) of histologically diagnosed invasive breast carcinoma. Material and methods: A prospective study of FNAC of breast lesions was carried out along with its histopathological correlation. All cases were diagnosed as invasive breast cancer in histopathological examination. All cytological breast cancer was evaluated for five features of invasive carcinoma. Results: We found that out of five predictive features Malignant Cells Adherent to stroma and Fibroblast Proliferation are most frequently seen in invasive breast carcinoma and their predictive value 78.26% for the both. Intracytoplasmic lumina in malignant cells and Fragments of elastoid stroma are the least features seen in invasive breast carcinoma and their predictive value 39.13% and 52.17%. Conclusion: In our study of prediction of invasion in breast carcinoma by FNAC, malignant cell adherent to stroma and Fibroblast proliferation are most consistent findings in invasive breast carcinoma. Intracytoplasmic lumina in malignant cells is least seen among breast carcinoma.